Penerapan Kebijakan Pembangunan Berkelanjutan di Lingkungan Kampus (Studi Perbandingan Antara Kampus Tembalang Universitas Diponegoro dan Kampus Tertre Universitas Nantes) - Fatmawati, Safrida; Syahbana, Joesron Alie (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
City is highly vulnerable to the impacts of climate change because of the large population, the intensive usage of infrastructure and a lot of economic activities. In addition, lifestyle and activity of urban communities, which neglect the impact of energy consumption, tend to increase the concentration of greenhouse gas involved in global warming. Improving the environment and the quality of life become the responsibility of all stakeholders, including the higher education institutions. They are the ones who have the contribution to conserve the environment. Sustainable Campus is a concept that began to develop in the world as a response to the environmental degradation which is integrated into the campus policy. This study proposes to compare the sustainable development policy within the Tertre campus, University of Nantes-France and Tembalang campus, Diponegoro University-Semarang, Indonesia. The material of this study was constituted through the interviews with the main stakeholders, as the key personnel in the field of sustainable development. In summary, we can conclude that the best sustainable development policy in the campus must be integrated into the environmental management, the improvement of the quality of life of the university community, and the strengthening of the economy, as well as engage in partnerships with all the stakeholders.